Arlo Smith for Attorney General Press Conference - Watkins, Howard::::::::: (1989)
Judy Soley speaking with Arlo Smith, Mike Idiart, ?, ?, ?, Holley Perez, Howard Watkins and 2 seated law enforcement officials watching